EFFECT OF TRINEXAPAC-ETHYL, AT TWO APPLICATION TIMINGS, ON THE INITIAL DEVELOPMENT OF EUCALYPTUS UNDER WATER DEFICIT - Bacha, A. L. [UNESP]; Martins, P. F. R. B. [UNESP]; Alves, P. L. C. A. [UNESP]; Paula, R. C. [UNESP] (Univ Federal Vicosa, 2019)
Eucalyptus plants are sensitive to stress during their initial development, and water deficit is the most important one. Thus, the hormctic effect caused by the application of chemical products may be a factor that allows plants to tolerate such stresses. The objective of this study was to evaluate the effects of trinexapac-ethyl on the initial growth of Eucalyptus urophylla (Clone I-144), under water deficiency, at two application timings (before planting - BP; and after planting - AP). Two experiments were conducted simultaneously in a greenhouse for 74 days after planting (DAP) eucalyptus in 15 L pots. Treatments consisted of three trinexapac-ethyl doses (0.0, 30, and 60 g a.i. ha(-1)) and two water conditions (with and without water deficit). A complete randomized block design was used, in a 3 x 2 factorial arrangement, with five replications. At the BP application timing, trinexapac-ethyl was sprayed at 0 DAP, and at the AP timing, at 24 DAP. In both experiments, plant height, diameter, leaf area, dry matter, total relative chlorophyll content and gas-exchange were evaluated. There was a positive effect for the net CO2 assimilation rate at 27 and 40 DAP, for AP and BP, respectively. Eucalyptus plants, without water deficit, presented higher growth, regardless of the application timing. In conclusion, the application of trinexapac-ethyl before planting caused a positive effect on the height and diameter of eucalyptus; and the application timing influenced, in different ways, the evaluated characteristics, not having harmful effects on any of them.
Keywords: Eucalyptus urophylla; hormesis; subdose; abiotic stress